Efektivitas acceptance commitment therapy untuk menurunkan tingkat depresi pada penderita gangguan depresi - Anggoro, Luke Setyo (Fakultas Psikologi Universitas Hang Tuah, 2025)
Depression is a mental disorder that significantly affects individuals’ quality of life and has shown an increasing prevalence in Indonesia. Managing depression requires a comprehensive and evidence-based approach, one of which is Acceptance and Commitment Therapy (ACT). ACT focuses on enhancing acceptance of negative thoughts and emotions while encouraging commitment to actions aligned with personal life values. This study aimed to examine the effectiveness of ACT in reducing depression levels among individuals with moderate to severe depression at the Efata Recovery Home in Salatiga. The study employed a quasi-experimental method using a one-group pretest–posttest design involving seven participants. Depression levels were measured using the Beck Depression Inventory-II (BDI-II) before and after the ACT intervention. Results of the paired sample t-test indicated a statistically significant reduction in depression levels (p < 0.05). The effect size analysis using Cohen’s d showed a moderate effect, suggesting that although ACT was statistically effective, its practical impact was moderate. These findings supported the evidence that ACT can serve as an effective psychological intervention for reducing depressive symptoms and provided a basis for applying acceptance-based therapies in mental health recovery setting in Indonesia.